(untitled) (American Journal of Islam and Society, 1999)
This article looks at the rationalist movement in the Muslim world in the earlier centuries of Islam and discusses the reasons for its imtial success and later setback. The article then discusses the implications of this setback for the revival of Islam and the ability of Muslim societies to meet successfully the challenges that they face in modern times.